Autumn migration of the White Stork, Ciconia ciconia, and the Black Stork, C. nigra, over the Bosphorus (Aves: Ciconiidae). Issue 2 (3rd April 2017) - Arslangündoğdu, Zeynel; Bacak, Ergün; Beşkardeş, Vedat; Dalyan, Cem; Smith, Luke; Payne, Margaret R.; Yardım, Ümit
Abstract : The Bosphorus is one of the main migration routes for soaring birds in Europe. Migrating White Storks and Black Storks have been counted at Büyük Çamlica hill in the four autumn seasons of 2006, 2007, 2008 and 2009 for 78 days each year. The numbers recorded are significantly lower than those counted in the1970's, and it is discussed whether this decline could be related to a change in migration routes caused by an increase in the size of the urban area of the City of Istanbul. The population of Istanbul has increased from 3.0 million in 1970 to 13.2 million in 2010.